Identification of Financial Risks in the Management of Commercial MSMEs in Villavicencio, Meta (GEON Journal (Management, Organizations and Business), 2022)
Problem: The article deals with the financial risks faced by MSMEs that carry out commercial activities in the city of Villavicencio, in the department of Meta, Colombia. The time horizon of analysis is from 2017 to 2019.   Objectives: To analyze the conditions in which MSMEs are facing the possible financial risks derived from their commercial operation. To review databases related to the commercial activity of the MSMEs under study, determine their operating conditions, as well as their relationship with possible financial risks, and determine relationships between market, liquidity, credit, and operation risks, in the analysis period.  Materials and methods: The research is descriptive and exploratory. Its approach is quantitative. The study is based, firstly, on the analysis of secondary sources based on data from chambers of commerce and; secondly, on the application of a survey with 19 items to a random sample of 31 MSMEs in the city of Villavicencio.  Results and discussion: In the period of analysis, the economic conditions of the MSMEs surveyed showed a situation of market equilibrium, which allowed them to have the necessary liquidity for proper management of their sources of self-financing and external funding in favor of the development of their business operations.  Conclusions: Market risks (customer-supplier relationship) represent the possible appearance of liquidity risks (delays in collections from customers and late payment to suppliers), which leads or does not lead to facing credit risks (access to external debt). The appearance of operational risks for MSMEs of commercial activity in Villavicencio depends on this sequence mechanism.  Contribution: The research was directed towards the continuous improvement and durability of micro, small and medium-sized enterprises, mainly those registered in commercial activities at the level of operations in cities with market characteristics similar to Villavicencio.
Keywords: commercial MSMEs; Villavicencio; credit risk; liquidity risk; market risk; operation risk